Sex differences on vestibular and ocular motor assessment in youth athletes - Moran, R. N.; Covassin, T.; Elbin, R. J. (Journal of Athletic Training, 2019)
Context The Vestibular/Ocular Motor Screening (VOMS) is a newly developed measure that evaluates vestibular and ocular motor symptom provocation after sport-related concussion. The effects of sex on baseline VOMS scores in youth athletes have not been established.